Lack of Offspring Nrf2 Does Not Exacerbate the Detrimental Metabolic Outcomes Caused by In Utero PCB126 Exposure - Rice, Brittany B.; Ngo Tenlep, Sara Y.; Tolaymat, Obadah; Alvi, Attaas T.; Slone, Fallon R.; Crosby, Claire L.; Howard, Stevi S.; Hermanns, Cecile L.; Montessorie, Nishimwe P.; Swanson, Hollie I.; Pearson, Kevin J. (Frontiers in Endocrinology, 2021)
Human environmental exposures to toxicants, such as polychlorinated biphenyls (PCBs), increase oxidative stress and disease susceptibility. Such exposures during pregnancy have been demonstrated to adversely affect offspring health outcomes. Nuclear factor erythroid-2-related factor 2 (Nrf2) regulates the antioxidant response and is involved in the detoxification of coplanar PCBs, like PCB126. The purpose of this study was to investigate glucose tolerance and body composition in PCB-exposed offspring expressing or lacking Nrf2. We hypothesized that offspring lacking Nrf2 expression would be more susceptible to the long-term health detriments associated with perinatal PCB exposure. During gestation, Nrf2 heterozygous (Het) and Nrf2 knockout (KO) mice were exposed to vehicle or PCB126. Shortly after birth, litters were cross-fostered to unexposed dams to prevent PCB exposure during nursing. Offspring were weaned, and their body weight, body composition, and glucose tolerance were recorded. PCB exposure resulted in a significant reduction in the average body weight of offspring born to Nrf2 Het dams (p < 0.001) that primarily arose from the decrease in average lean body mass in offspring (p < 0.001). There were no differences in average body weight of PCB-exposed offspring born to Nrf2 KO dams (p > 0.05), and this was because offspring of Nrf2 KO dams exposed to PCB126 during pregnancy experienced a significant elevation in fat mass (p = 0.002) that offset the reduction in average lean mass (p < 0.001). Regardless, the lack of Nrf2 expression in the offspring themselves did not enhance the differences observed. After an oral glucose challenge, PCB-exposed offspring exhibited significant impairments in glucose disposal (p < 0.05). Offspring born to Nrf2 Het dams exhibited these impairments at 30 min and 120 min, while offspring born to Nrf2 KO exhibited these impairments at zero, 15, 30, 60 and 120 min after the glucose challenge. Again, the interactions between offspring genotype and PCB exposure were not significant. Surprisingly, these findings demonstrate that the lack of offspring Nrf2 expression does not worsen the metabolic derangements caused by in utero PCB exposure. Future directions will focus on understanding how the observed maternal Nrf2 genotypic differences can influence offspring metabolic responses.